2012
DOI: 10.1177/0021998312446500
|View full text |Cite
|
Sign up to set email alerts
|

Damage characterization of quasi-statically indented composite sandwich structures

Abstract: The nature of quasi-static indentation damage is studied in aluminum honeycomb core sandwich panels with eight ply, quasi-isotropic, graphite/epoxy face sheets. Parameters that are varied include the core thickness, core density, face sheet layup, and indentor diameter. The majority of induced damage is in the vicinity of the barely visible threshold. The permanent dent in the panel is found to be always larger than the contact area of the indentor, and specimens with denser cores exhibit smaller dent diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(51 citation statements)
references
References 22 publications
2
49
0
Order By: Relevance
“…The objective is to determine the effects of core thickness, core density, face sheet stacking sequence, face sheet thickness, and indentor diameter on the nature and extent of damage, to establish the various physical mechanisms at work, and to deduce certain guidelines that may be useful in the design of damage resistant structures. Many of the results already published in Singh et al 21 for the eight ply case are presented again in combination with the 16 ply results in this paper. This approach is taken in order to help make comparisons easier between the eight and 16 ply results.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…The objective is to determine the effects of core thickness, core density, face sheet stacking sequence, face sheet thickness, and indentor diameter on the nature and extent of damage, to establish the various physical mechanisms at work, and to deduce certain guidelines that may be useful in the design of damage resistant structures. Many of the results already published in Singh et al 21 for the eight ply case are presented again in combination with the 16 ply results in this paper. This approach is taken in order to help make comparisons easier between the eight and 16 ply results.…”
Section: Introductionsupporting
confidence: 68%
“…Perhaps due to the large overall sandwich panel thickness, the through-transmission approach produced relatively poor results. For the pulse-echo technique, transducer frequencies from 5 to 50 MHz were evaluated and the results compared to each other and to destructive examinations, similar to those described in Singh et al 21 Interestingly, the 50 MHz transducer was found to produce the best overall assessments for both face sheet thicknesses. It gave the most information near the indented surface, the most clarity for the delaminations observed, and it penetrated essentially the same depth into the specimen (approximately 11 plies) as the lower frequency transducers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1]. Delamination and debonding -in general -is induced by impact [2][3][4][5][6][7][8][9][10], blast loading [11], drilling and perforation [12,13] or indentations [14][15][16] or other special loads [17,18]. Moreover, delaminations can change significantly the buckling behaviour of laminated structures [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%